Dural ectasia in Loeys–Dietz syndrome: comprehensive study of 30 patients with a TGFBR1 or TGFBR2 mutation. (17th December 2013) - Sheikhzadeh, S.; Brockstaedt, L.; Habermann, C.R.; Sondermann, C.; Bannas, P.; Mir, T.S.; Staebler, A.; Seidel, H.; Keyser, B.; Arslan‐Kirchner, M.; Kutsche, K.; Berger, J.; et al.
<x xml:space="preserve">Abstract</x> The purpose of this study was to assess the frequency, severity, and clinical associations of dural ectasia (DE) in Loeys–Dietz syndrome (LDS). Database analysis of three German metropolitan regions identified 30 patients with LDS and TGFBR1 mutation in 6 and a TGFBR2 mutation in 24 individuals (17 men; mean age: 31 ± 19 years), as well as 60 age and sex‐matched control patients with Marfan syndrome carrying a FBN1 mutation. DE was present in 22 patients with LDS (73%), and it related to skeletal score points (p = 0.008), non‐skeletal score points (p < 0.001), and to the presence of ≥7 systemic score points (p = 0.010). Similarly, the severity of DE was related to body height (p = 0.010) and non‐skeletal score points (p = 0.004). Frequency (p = 0.131) and severity of DE (p = 0.567) was similar in LDS and Marfan syndrome. DE is a manifestation of LDS that occurs with similar frequency and severity as in Marfan syndrome. Severity of DE may serve as a marker of the overall connective tissue disease severity. LDS may be considered in patients with DE.